Herpes Zoster + Scabies Krustosa Pada Pasien Diabetes Militus - Azman Bripo; Muhammad Mimbar Topik (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Herpes zoster and crusted scabies are dermatological conditions that pose a higher risk and clinical severity in immunocompromised patients, particularly those with chronic comorbidities such as diabetes mellitus and hypertension. This case report presents a 55-year-old woman with painful vesicular eruptions on the right neck and generalized thick, crusted, itchy plaques across the body. She had a longstanding history of type 2 diabetes mellitus and hypertension. Clinical diagnosis of herpes zoster and crusted scabies was confirmed through physical examination and KOH microscopic testing, which identified Sarcoptes scabiei. The patient was treated with oral acyclovir, topical permethrin, and supportive therapy to manage pain and prevent secondary infections. The coexistence of herpes zoster and crusted scabies in a diabetic patient highlights the role of impaired immunity in disease severity and presentation. Early recognition and integrated management are essential to improve prognosis and prevent complications.